PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PT. SEMEN PADANG ( STUDI PADA DEPARTEMEN SDM ) - Kemal Aldian Faldano; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at PT. Semen Padang Jl. Raya Indarung Padang, West Sumatra. The purpose of this study was to determine the effect of transformational leadership style on employees performance at the HR department of PT. Semen Padang. Transformational leadership style as the independent variable (X) and employees performance as the dependent variable (Y).The problem in this research is that the performance of the HR department employees is still fluctuating and has not reached the predetermined target because the realization has not shown a significant increase each year. The sample of this study was taken as many as 38 respondents from the population calculated using the census method. Data obtained from the results of a questionnaire distributed in the HR department of PT. Semen Padang. The analysis technique used is simple linear regression, the coefficient of determination, and t test.The results of tests conducted indicate that the tranformational leadership style on  leader of  HR departement and the employees performance in good category. Based on T test transformasional leadership atyle has a significant  effect  on  the employees performance. And for the coefficient of transformasional  leadership  style has a significant effect on the employees performance with R square value  0.123. that thing conducted  the transformational leadership style  has give  effect  12,3 %  on employees performance and 87,7% has determined of other variable  that is not include of this research. Keywords: Transformational Leadership Style, Employees Performance